Implementation of Performance Accountability System For Government Institution (SAKIP) : Determinants and Consequence In Local Government - Telabah, I Wayan Suardana; Hermanto, Hermanto; Handajani, Lilik (International Business and Accounting Research Journal, 2018)
This study aims to examine the effect of the utilization of information technology, training and obedience to regulation on the implementation of SAKIP and examine the effect of SAKIP implementation on managerial performance as well as the influence of the role of self efficacy and intellect in the relationship between impelementation of SAKIP and managerial performance. Tests were conducted on 93 respondents representing 67 percent of the population. The group of respondents are structural officials of echelonÂ  II, III and IV in the scope of West Nusa Tenggara Provincial Government who have role in the planning, implementation and management of Regional Income Budget and Expenditure (APBD) through the implementation of SAKIP. The hypothesis testing used Structural Equation Modelling-Partial Least Square (SEM-PLS). The result of this research shows that the utilization of information technology and training have significant effect on the implementation of SAKIP but not influenced by obedience to the regulation, the implementation of SAKIP has an effect on managerial performance but self efficacy and intellect can not strengthen the relationship between SAKIP implementation and managerial performance. Based on the findings of this research, the operation of e-SAKIP and training conducted in a structured and sustainable manner plays an important role in improving the quality of SAKIP implementation so as to provide relevant and objective information to managers in order to improve the performance of government organizations.